EVALUATION OF PAIN SCALE ON CIRCUMCISION PATIENTS UNDER LIDOCAINE HYDROCHLORIDE LOCAL ANESTHESIA - Aulia Achmad, Baraz; Manela, Citra; Zulfiqar, Yevri; Hendriati; Effendi, Rinal; Myh, Etriyel (Indonesian Journal of Urology, 2025)
Objective: Evaluating the pain scale of circumcision patients under lidocaine hydrochloride local anesthesia. Material & Methods: An observational descriptive research was carried out on 30 children with a body weight of 20-29 kilograms from February 2023-April 2023. Circumcision was performed under 2 ampoules of 2% lidocaine as local anesthesia. Data consisted of pain onset measure using a stopwatch and the pain scale were obtained through the Wong-Baker Face Pain Rating Scale (WBFPRS), these variables were recorded when pain occurs post-local anesthesia effects ends. Results: The average onset of pain is 47.73 minutes with the fastest onset of pain was 20 minutes and the longest onset of pain was 72 minutes. The average pain scale as measured by the WBFPRS is 2.33. Conclusion: The average pain scale in this study was less than 3 which indicated that the pain felt did not interfere with activities. Keywords: Circumcision, pain, anesthesia, lidocaine.